Promising activity of pencycuron, a phenylurea-based fungicide, for effective management of black scurf of potato - and SWEETY KAUR, T.S. THIND, CHANDER MOHAN (Indian Phytopathology, 2012)
Pencycuron, a phenylurea-based fungicide, caused total inhibition of mycelial growth of Rhizoctonia solani at 25 j..Iglml and was found most effective in checking black scurf of potato. Its formulations monceren 250 SC and monceren 25 WP provided almost complete control of the disease when used as dip treatment at 0.5 and 0.75% concentrations under pot house and field conditions during 1999- 2000and 2000-2001 crop seasons. Emisan-6 (MEMC) @ 0.25% appeared next in order of efficacy. Vitavax75 WP, though found to be highly inhibitory in vitro, but did not control the disease as effectively in pot house and in field. The efficacy of bavistin (0.3%) was at par with vitavax 75 WP (0.5%). Vitavax 200 WP (0.35%)appeared to be slightly more effective than vitavax 75 WP (0.25 and 0.5%). Boric acid (3%), though provided 66.5% disease control, but showed slightly adverse effect on tuber germination, plant height and yield. Kitazin (0.1 and 0.2%) proved to be least effective. Both the formulations of pencycuron did not show any adverse effect on plant growth parameters and can serve as effective and safer alternative to the hazardous mercurial fungicides for the management of black scurf of potato.